2011
DOI: 10.1080/03004430.2010.501407
|View full text |Cite
|
Sign up to set email alerts
|

Turkish preschool teachers' beliefs on integrated curriculum: integration of visual arts with other activities

Abstract: This study investigates preschool teachers' beliefs about integrated curriculum and, more specifically, their beliefs about integration of visual arts with other activities. The participants of this study consisted of 255 female preschool teachers who are employed in preschools in Ankara, Turkey. For the study, teachers were asked to complete 'teachers' beliefs about integration of visual arts questionnaire'. The questions in the instrument were constructed as open-ended and closed-ended. Results indicated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
0
6
0
4
Order By: Relevance
“…Many studies showed that an integrated curriculum was able to support the whole child model by providing different types of activities (visual, linguistic, and physical), in order to improve their holistic development (Schirrmacher, 2002;Walker, 1995). Similarly, Öztürk and Erden (2010) found that early childhood teachers used integrated activities because it addressed children's different developmental areas such as physical, cognitive, and social development.…”
Section: Discussionmentioning
confidence: 97%
“…Many studies showed that an integrated curriculum was able to support the whole child model by providing different types of activities (visual, linguistic, and physical), in order to improve their holistic development (Schirrmacher, 2002;Walker, 1995). Similarly, Öztürk and Erden (2010) found that early childhood teachers used integrated activities because it addressed children's different developmental areas such as physical, cognitive, and social development.…”
Section: Discussionmentioning
confidence: 97%
“…For this reason, high-level of thinking and approaching the problems with different perspective could be provided and rich learning environments could be created (McComas & Wang, 1998). Interpretation of gathered information could be made easier (Kaya, Akpınar & Gökkurt, 2006;Öztürk & Tantekin Erden, 2011). There are different ways of merging disciplines in an educational aim.…”
Section: Introductionmentioning
confidence: 99%
“…It is understood that this sense of art does not address only affective aspects but also improve the cognitive skills (observation, perception, interpretation, synthesizing, creative-thinking, critical perspective, etc.) (Çapar, 2006;Öztürk & Tantekin Erden, 2011;San, 2001). By discovering this effect of art, today, education of maths, social studies, science, history, foreign language etc.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations